Exploring the relationships between adolescent alcohol misuse and later life health outcomes. (17th September 2022) - Pascale, Angela; Stephenson, Mallory; Barr, Peter; Latvala, Antti; Aaltonen, Sari; Piirtola, Maarit; Viken, Richard; Rose, Richard J.; Kaprio, Jaakko; Maes, Hermine; Dick, Danielle M.; Salvatore, Jessica E.
Abstract: Background: We sought to clarify the impact of adolescent alcohol misuse on adult physical health and subjective well‐being. To do so, we investigated both the direct associations between adolescent alcohol misuse and early midlife physical health and life satisfaction and the indirect effects on these outcomes attributable to subsequent alcohol problems. Method: The sample included 2733 twin pairs (32% monozygotic; 52% female) from the FinnTwin16 study. Adolescent alcohol misuse was a composite of frequency of drunkenness, frequency of alcohol use, and alcohol problems at ages 16, 17, and 18.5. The early midlife outcomes included somatic symptoms, self‐rated health, and life satisfaction at age 34. The mediators examined as part of the indirect effect analyses included alcohol problems from the Rutgers Alcohol Problem Index at ages 24 and 34. Serial mediation and co‐twin comparison models were applied and included covariates from adolescence and early midlife. Results: There were weak direct associations between adolescent alcohol misuse and early midlife physical health and life satisfaction. However, there was stronger evidence for indirect effects, whereby young adult and early midlife alcohol problems serially mediated the relationship between adolescent alcohol misuse and early midlife somatic symptoms ( β = 0.03, 95% CI [0.03, 0.04]), self‐rated health ( β = −0.02, 95% CI [−0.03, −0.01]), and life satisfaction ( β = −0.03, CI [−0.04, −0.02]). These serial mediation effects were robust in co‐twin comparison analyses. Conclusions: These results provide evidence that alcohol problems are a primary driver linking adolescent alcohol misuse and poor health outcomes across the lifespan. Abstract : In a sample of 2, 733 twin pairs from Finland, we found evidence that young adult and early midlife alcohol problems serially mediate the relationship between adolescent alcohol misuse and higher somatic symptoms, lower self‐rated health, and lower life satisfaction in early midlife. These effects were robust following rigorous control for potentially confounding genetic and environmental factors using a co‐twin comparison design. These findings indicate alcohol problems are a primary driver linking adolescent alcohol misuse and poor health outcomes across the lifespan.